The Moral Burden of Memory: The Role of National Narratives in Democracy Building - Marsoobian, Armen T. (Տիգրան Մեծ)
This essay is a meditation on memory and democracy. I will argue that democracy as a way of life is condi-tioned upon how well a community remembers its past. The concept of democracy as a way of life, as distinct from a particular form of governance, has its origins in the political philosophy of John Dewey. I will approach this issue in a somewhat roundabout manner. In the first part, I will examine a series of Dewey’s writings from the early 1920s that resulted from his visit of the newly established Republic of Turkey. I contend that the se-rious shortcomings in Dewey’s analysis of Turkish state nation-building highlight deficiencies in his otherwise laudable and nuanced democratic theory. In the second part, I provide a more sustained analysis of the role of collective memory within a community, especially one that aspires to a democratic way of life. I will then con-clude with a few reflections upon issues arising from Turkish collective memory in relation with the Armenian Genocide.
Keywords: Armenian genocide